2018
DOI: 10.6007/ijarbss/v8-i12/5055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between World Oil Price and Exchange Rate on Agricultural Commodity Prices in Indonesia

Abstract: Increasing food prices in the world caused a global food crisis. Some Asian countries are also affected by rising world food prices, including Indonesia. Using Vector Error Correction Model (VECM) method, the researchers intend to analyze the long-term relationship between world oil price and exchange rate to agricultural commodity price (rice, corn and soybean) in Indonesia and test whether there is an existing causality. This analysis is based upon the data set covering the monthly period of January 2010 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The results of the study related that volatility spill-over is significant from the crude oil market to commodity markets and volatility in crude oil prices always affect the futures prices of agricultural commodities. [28] used VEC model followed by Granger Causality test and Impulse response funtion to investiagte the impact of oil price on rice spot prices in Indonesia. The study found long term unidirectional causality running from oil price to the rice spot prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the study related that volatility spill-over is significant from the crude oil market to commodity markets and volatility in crude oil prices always affect the futures prices of agricultural commodities. [28] used VEC model followed by Granger Causality test and Impulse response funtion to investiagte the impact of oil price on rice spot prices in Indonesia. The study found long term unidirectional causality running from oil price to the rice spot prices.…”
Section: Literature Reviewmentioning
confidence: 99%